A internação do adolescente em conflito com a lei como "única alternativa" : reedição do ideário higienista - Feitosa, Juliana Biazze (2011)
This objective study to evaluate the existence of contained aspects of the hygienism in the justifications of the sentences judicial of adolescents who fulfill the internment Social-educational and if it characterizes as a historical research. The violence and crime, for its visibility, come being considered as one of the main faced social problems in Brazil beeing a comum thing it is had participation of adolescents in the practical one of gravity crimes. The Statute of the Child and the Adolescent, legislation that regulates youthful-children justice in Brazil, foresees to the adolescent authors of infraction act the fulfilment of the partner education measures, namely: warning, obligation to repair the damage, rendering of services to the community, attended freedom, semifreedom and the internment; focus of this study. The related law praises that the internment in educational establishment will have to be applied in last instance and when it will not have another adjusted social education measure more. However, in general, the studies carried through on this thematic one have shown that the internment is the reply that the society offers to face the problem of the involvement of adolescents in practical of torts and the too much social problems, as much in the present time as in the past. It is worth remembering that the commission of infractions for children and adolescents is not proper of the present time and that has registers of them Imperial period no longer and mainly in the first decades of the instauration of the Republic. They are these events of the past and the gift registered in literature and divulged by the media daily that they had taken in them to carry through a research on the interventions proposals in the present time to face the practical one of youthful infractions, that is in part materialized in the sentences judicial. In this direction, we analyze twenty - one (21) sentences that determine the internment and the respective materials of support that composes the action at law of adolescents who had given entered in the year of 2010 in the Center of Social education II of Cascavel in the State of the Paraná - CENSE II of Cascavel - PR, one of the entities of the State of the responsible Paraná for the execution of the social education internment. To analyze the collected data we take as orientation the history inspired by the Marxian source. The results reached had taken in us to conclude that in the present time, although the Statute of the Child and the Adolescent and the institutions counting on a new physical and organizacional structure, we continue, definitive for sentence judicial, removing the adolescent of the situation of bad behavior and locked up the judicial stated period returning it for the same context of where it was removed. Protected the had differences of form and time one notices in this guiding aspects of the principles of the ideas of hygienist and the minor doctrine. Nowadays we evidence that the fact to have an advanced legislation and the Centers of Socio education to count on a multi-professional team were not reverted in reduction of the number and of the gravity of the infractions, for the opposite, the official data indicate that had an increase of serious infractions practised by these adolescents - of small roberies they had started to commit robberies, traffic of drugs, and homicides. In these terms, it is possible to affirm that other answers are necessary to face the infant-youthful violence, that certainly exceed the practical one of the imprisonment directed in the principles of the ideas of the mental hygiene.